2016
DOI: 10.1016/j.actamat.2016.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Incipient slip and long range plastic strain localization in microtextured Ti-6Al-4V titanium

Abstract: High resolution scanning electron microscope digital image correlation (SEM DIC) was performed in situ during uniaxial loading on Ti-6Al-4V rolled sheet titanium to determine the dependence of strain localization on microstructure and microtexture. Individual grains with preferred orientation for basal slip exhibited plastic localization along basal planes before macroscopic yielding. With additional strain, but still below macroscopic yielding, pyramidal and prismatic plastic activity was observed as slip ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(66 citation statements)
references
References 34 publications
(40 reference statements)
7
58
0
Order By: Relevance
“…For example, Bridier et al [6] have demonstrated slip transmission between primary-alpha and secondary-alpha colonies. Recently, Echlin et al [7] have highlighted the development of multi-alpha-particle slip bands traversing entire MTRs. Hence, it is important to have models available to simulate microstructure evolution at each length scale.…”
mentioning
confidence: 99%
“…For example, Bridier et al [6] have demonstrated slip transmission between primary-alpha and secondary-alpha colonies. Recently, Echlin et al [7] have highlighted the development of multi-alpha-particle slip bands traversing entire MTRs. Hence, it is important to have models available to simulate microstructure evolution at each length scale.…”
mentioning
confidence: 99%
“…However, large amount of Moiré fringes were observed in the major α plate, as shown in Fig. 5 (a), indicating the shear of a 21 of the major α plate may be absorbed mainly by its prismatic slip [41,42], as it is well known that the prismatic slip of the α phase of the Ti has very small critical resolved shear stress (CRSS) [43,44]. Obviously the interface α particles further serve as sympathetic nuclei for the formation of the neighboring major α plate with the same orientation and eventually contribute to formation of the triangular variant cluster of three 60°/<11 0> α inter-2 related major α plates, as shown in Fig.…”
Section: Formation Of Interface α and Local Variant Selection Of Major αmentioning
confidence: 94%
“…In Figure 2b, the compression direction is 45 • to the rolling direction (RD) and ND and will be referred to as the 45 • compression case later. RD, ND, and TD (transverse direction) were determined such that the ND pole figures coincided with the experimental measurement [17,18]. Note that both the compression direction and MTR orientation were changed in the mesoscale simulations, such that the uniaxial compression boundary condition can be conveniently applied, and the angle between the MTR axis and compression axis is the same as in the high temperature compression experiment [13,15].…”
Section: Hierarchical Multiscale Modeling Frameworkmentioning
confidence: 98%
“…A statistically equivalent representative volume element (RVE) was generated as the microscale model for hierarchical multiscale modeling. The initial orientation distribution and α p particle size distribution were prescribed from typically observed texture components in Ti-6242 [15,17,18]. An equivalent orientation distribution function (ODF) was calculated based on the EBSD (electron backscatter diffraction) measurement using the open source software MTEX [19].…”
Section: Statistically Equivalent Microstructurementioning
confidence: 99%
See 1 more Smart Citation